Extremely Low Dark Current MoS2 Photodetector via 2D Halide Perovskite as the Electron Reservoir. Issue 6 (13th January 2020) - Wang, Haoliang; Wang, Xudong; Chen, Yan; Zhang, Shukui; Jiang, Wei; Zhang, Xin; Qin, Jiajun; Wang, Jiao; Li, Xiaoguo; Pan, Yiyi; Liu, Fengcai; Shi, Zejiao; et al.
Abstract: Toward pursuing high‐performance photodetectors based on 2D transition metal dichalcogenides (TMDs) such as molybdenum disulfide (MoS2 ), it is desirable to reduce the high dark current and sluggish response time. Here, in multilayer MoS2 ‐based photodetectors, a 2D halide perovskite, (C6 H5 C2 H4 NH3 )2 PbI4 ((PEA)2 PbI4 ), is introduced as a bifunctional material: both as electron reservoir to reduce free carriers and passivation agent to passivate defects. Surprisingly, dark current is suppressed by six orders of magnitude after coating a (PEA)2 PbI4 thin layer onto pristine MoS2 photodetector, with the dark current decreased to 10 −11 A. This huge reduction of dark current suggests an efficient interlayer charge transfer from MoS2 to (PEA)2 PbI4, which is further verified by photoluminescence quenching phenomenon. It indicates that (PEA)2 PbI4 serves as electron reservoir to reduce carrier density of MoS2, resulting in ultrahigh detectivity (1.06 × 10 13 Jones). Moreover, the response speed is also accelerated by more than 100‐fold due to passivation by 2D perovskite. In addition, it is found that this type of photodetectors can further work at self‐power mode (with the bias of 0 V). Therefore, the strategy of applying 2D perovskite on the surface of TMDs provides a novel way to fabricate high‐performance photodetectors. Abstract : By delicately introducing 2D perovskite on the MoS2 surface, the performance of the MoS2 photodetector is greatly improved. The perovskite can act both as electron reservoir to reduce free carriers and passivation agent to passivate defects. This combination will greatly suppress the dark current in pristine MoS2 photodetectors, increase the photoresponse on/off ratio, and decrease the photoresponse time.